Hubungan Kesesakan Dengan Kesejahteraan Psikologis PAda Masyarakat Yang Tinggal Di Kawasan Kelayan Kota Banjarmasin - Saputra, Jupri Handi (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
In essence, humans always have the desire to be able to live their lives well and prosper both physically and psychologically (psychological well-being), but on the other hand the increasing population growth in an area also increases the need for housing so as to cause density, this can trigger an increasing perception of distress (crowding). ) in society which leads to a decline in psychological well-being for affected individuals. The purpose of this study is to determine how the relationship between the perception of distress and psychological well-being in the Central and East Service Villages with a correlational quantitative approach as well as the Product Moment Person correlation analysis method and regression test to reveal the influence of perceived distress on psychological well-being. The respondents in this study were 270 residents of Kelurahan Kelayan Tengah and Kelayan Timur. Respondents were determined using the cluster random sampling method. The data were collected using two scales, namely the scale of perception of distress and the scale of psychological well-being. In this study, it was found that there was a negative relationship between the perception of distress and psychological well-being in the community in the Banjarmasin City area with a significance value of 0.000 and a pearson correlation of -0.422. The study concluded that if the individual perceives the density of his environment as something unpleasant or in this is a distress then it will lower his level of psychological well-being.